Project Report on Secure and Safety Mobile Network for Visually Impaired People - MEENA H B, ROOPA V, SHYAMA K and VIJAYALAKSHMI (2012)
INTERNAL GUIDE: T MALAVIKA, MVJCE
Keywords: Visually Impaired People